Optimización de los parámetros tecnológicos para la extracción, caracterización y microencapsulamiento por atomización de la pulpa integral de ungurahui (Oenocarpus bataua) - Saavedra Rios, Robert Hendrik (2024)
In the present study, the objective was to optimize the parameters for the extraction, characterization and microencapsulation of bioactive compounds from the whole pulp of Ungurahui (Oenocarpus bataua). The hydroethanolic extraction process by maceration using a rotational composite central design of response surface methodology (RSM) was used to determine the optimal extraction conditions, using absolute ethanol concentration (0-100%) and maceration time (2-6 days) as factors. The optimum extraction conditions (50:50 ethanol: water and 6 days) promoted obtaining the highest percentage of compound yield (RE): 4.03±0.05%, total phenolic content (TP): 1330.40±10.55 mg EAG/g DM, ABTS 8526.68±14.34 µmol Trolox/g DM, DPPH 1209.52±26.00 µmol Trolox/g DM and anthocyanins 29.76±0.24 mg C3G/g DM. Encapsulation of the extract with gum arabic using spray drying produced micrometric-sized microparticles (26.54±09.73 μm), irregular in shape, 4.54±0.60% moisture, 92.45±1.09% solubility, 4.67±0.41% hygroscopicity and electronegative zeta potential of -0.23±0.04 mV. The results obtained in the present study provide an adequate alternative for the extraction of bioactive compounds and the corresponding production of microparticles by spray drying, for the incorporation of bioactive compounds with antioxidant properties in the generation of new products for the food industry.